2017
DOI: 10.1016/j.eurpsy.2017.01.1886
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Association Between Glutamatergic Genes and Sri Treatment Response in Obsessive Compulsive Disorder

Abstract: IntroductionPharmacogenetic studies in obsessive-compulsive disorder (OCD) primarily focussing on serotonergic and dopaminergic polymorphisms, provided inconsistent findings. There is recent evidence for glutamatergic abnormalities in OCD.AimsExamine the association glutamatergic genes with serotonin reuptake inhibitor (SRI) response in OCD.ObjectivesTo study pharmacogenetic association between SLC1A1 and GRIN2B polymorphisms with SRI response in OCD.MethodsDSM-IV OCD patients were recruited from a specialty O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With respect to the regression analysis, PRS was not a predictor for treatment response in our sample. Some evidences exist about the non-shared genetic bases of OCD risk and OCD treatment response 22,55 . In addition, although other studies have found an association between OCD treatment response and genes previously associated to OCD risk 14,15,19 (such as SLC1A1, SLC6A4 or BDNF 12,13 ), to our knowledge, only one genetic variant (rs3087879 in SLC1A1 gene) has been related to both OCD treatment response (a greater resistance) and OCD risk 12 .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the regression analysis, PRS was not a predictor for treatment response in our sample. Some evidences exist about the non-shared genetic bases of OCD risk and OCD treatment response 22,55 . In addition, although other studies have found an association between OCD treatment response and genes previously associated to OCD risk 14,15,19 (such as SLC1A1, SLC6A4 or BDNF 12,13 ), to our knowledge, only one genetic variant (rs3087879 in SLC1A1 gene) has been related to both OCD treatment response (a greater resistance) and OCD risk 12 .…”
Section: Discussionmentioning
confidence: 99%